Fábrica de pastores: interfaces e divergências entre educação teológica e fé cristã comunitária na teologia pentecostal - Pommerening, Claiton Ivan (2015)
The formal reflective theology was a rejection target in the beginning of Pentecostalism since it presented an anti-intellectualist culture and of experiential religiosity. It was built primarily in oral and narrative form. As Pentecostalism was growing and taking shape in Brazil, with the adherence of more illustrious elements of society, it began to give opening to a more rational and elaborated theological reflection. However, the initial rejection assumptions continued latent, albeit in covert and subjective form making important theological advances difficult, especially in regards to the Assemblies of God. This research aims to clarify through historical research which leads to sociological and theological contributions, the advances and retreats that theological education undertook in the Assemblies of God in Brazil, detailing discussions between supporters and disapprovers of theological education, approaching the elaboration of curriculums and the dispute among Swedish, Brazilians and North-Americans for the theological education, the foundation enterprises of biblical institutions and theological courses by extension and expansion of theology until courses recognized by MEC were opened, which nowadays are supported by some Assemblies of God in Brazil. It tries to explain why Pentecostalisms prefer theologies with a more devotional and experiential character in detriment of more reflective and critical theologies, taking in consideration the emphasis given to theology of pneumatological character. For such, the importance of the ecstasy phenomenon through the baptism in the Holy Spirit and all the experiential manifestations of this religious segment is demonstrated and proposes a theological method that tries to reconcile the Pentecostal theological legacy with academic and reflective theologies in an attempt to draw a possible path for the Pentecostal theology that is still in development.